The Effect of Red Spinach Juice and Honey on Increasing Hemoglobin Levels in Trimester II and III Pregnant Women at the Lempake Health Center in Samarinda - Ika Dewi Kusuma; Umi Kalsum; Nursyahid Siregar (Formosa Journal of Science and Technology, 2023)
Anemia is a condition in which the body has too few red blood cells. This study analyzed the effect of red spinach juice and honey on increasing hemoglobin levels in pregnant women in the second and third trimesters at the Lempake Health Center in Samarinda. The research method is Quasi Experiment with Pretest-Posttest with Control Group Design. A total sample of 20 respondents was carried out from 15 June to 15 July 2022. The results of the t-test research obtained a p-value of 0.000 <0.05. Discussion: This can happen because the content of vitamins and iron in red spinach and honey will help the intake of iron needed by pregnant women. Conclusion: Red spinach juice and honey can increase hemoglobin levels in pregnant women in the second and third trimesters.